Study guide: HBEC2603 teaching English to young learners - Badzis, Mastura (Open University Malaysai (OUM), 2012)
This course describes the four fundamental developmental areas of a child’s language arts – speaking, listening, reading and writing – in the context of teaching a second language or an additional language to young children in early childhood settings. The learning process for young learners is different from older learners, so, as teachers, you need to adopt different attitudes, approaches and techniques in your teaching. You also need to understand and be able to implement the appropriate language curriculum for young classroom as well as skilful in assessing their language learning process.